Investigation of DNA Damage and Cell-Cycle Distribution in Human Peripheral Blood Lymphocytes under Exposure to High Doses of Proton Radiotherapy - Justyna Miszczyk (Biology, 2021)
This study systematically investigates how a single high-dose therapeutic proton beam versus X-rays influences cell-cycle phase distribution and DNA damage in human peripheral blood lymphocytes (HPBLs). Blood samples from ten volunteers (both male and female) were irradiated with doses of 8.00, 13.64, 15.00, and 20.00 Gy of 250 kV X-rays or 60 MeV protons. The dose–effect relations were calculated and distributed by plotting the frequencies of DNA damage of excess Premature Chromosome Condensation (PCC) fragments and rings in the G2/M phase, obtained via chemical induction with calyculin A. The Papworth’s u test was used to evaluate the distribution of DNA damage. The study shows that high doses of protons induce HPBL DNA damage in the G2/M phase differently than X-rays do. The results indicate a different distribution of DNA damage following high doses of irradiation with protons versus photons between donors, types of radiation, and doses. The proliferation index confirms the impact of high doses of mitosis and the influence of radiotherapy type on the different HPBL response. The results illuminate the cellular and molecular mechanisms that underlie differences in the distribution of DNA damage and cell-cycle phases; these findings may yield an improvement in the efficacy of the radiotherapies used.